Strategy to respond gratification by identifying gift-giving to government employee - Lisa Nazifah (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2019)
Gratification often called as the root of corruption. Gift-giving is usually considered a common tradition that has been entrenched in community life in Indonesia. However, it should be confirmed that even the slightest gift to civil servants or state administrators can be considered as an act of bribery if the gift is related to their position and contrary to their obligations or duties. Numerous gratification practices that lead to bribery have still been found indicating the lack of understanding and intention of civil servants in addressing gratification based on the regulation applied. The study is performed using qualitative descriptive methods with a description of the topic related. Data collected by observing study group discussion at Diklat Prajabatan for a non-permanent teacher in DKI Jakarta year 2018. The identification of gratification can be self-performed by recognizing the motive of the gift-giving act using PROVE IT (Purposes, Rule, Openness, Value, Ethics, Identity, and Timing). Besides, the improved understanding of the rights and obligations as a public servant as well as the change of mindset would initially provide the capability for every civil servant and state administrators in addressing gratification wisely and applicably. The integrity of civil servants is an indicator of a clean and corruption-free government that leads to good and accountable governance.